2012
DOI: 10.1016/j.bone.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A novel library screen identifies immunosuppressors that promote osteoblast differentiation

Abstract: Bone homeostasis can be compromised by an increase in osteoclast-mediated resorption and/or a decrease in osteoblast-mediated bone deposition. While many efforts have focused on treating osteoclast resorption, there has been less emphasis on identifying strategies for promoting osteoblast function. Herein, we describe a high-throughput screening assay to select for small molecules that augment bone morphogenetic protein-2 (BMP-2)-mediated osteoblast lineage commitment. After an initial screen of 5405 compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 63 publications
1
46
1
Order By: Relevance
“…Previous report found that rapamycin promotes osteoblast differentiation and inhibition of autophagosome formation in a mouse model showed severe osteopenia (Darcy et al., 2012; Shimada, Greer, McMahon, Bouxsein, & Schipani, 2008). Similarly, rapamycin has been proven to be able to reduce the severity of age‐related bone changes in trabecular bone of older male rats by partially activating autophagy of osteocytes (Luo, Ren, Li, Lian, & Lin, 2016), which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous report found that rapamycin promotes osteoblast differentiation and inhibition of autophagosome formation in a mouse model showed severe osteopenia (Darcy et al., 2012; Shimada, Greer, McMahon, Bouxsein, & Schipani, 2008). Similarly, rapamycin has been proven to be able to reduce the severity of age‐related bone changes in trabecular bone of older male rats by partially activating autophagy of osteocytes (Luo, Ren, Li, Lian, & Lin, 2016), which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…This trend was also seen in the trabecular bone of the lumbar vertebra where a slightly higher bone volume and trabecular thickness were observed. It has been suggested that the modulation of mTOR may activate signaling events which would prevent the progression of lytic bone disease (Smink & Leutz, 2010) and can enhance the proliferation and differentiation of osteoblasts (Darcy et al , 2012). To fully determine whether rapamycin may attenuate bone aging, further studies with chronic rapamycin treatment beginning prior to any significant loss of bone due to aging (~3 months of age for C57BL/6 mice) are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…However, CXCR4 blockade (AMD3100) alone was not successful, and the addition of low dose FK506 was essential, perhaps exerting its effect via the FK506-binding protein 12 (FKBP12) and not by calcineurin inhibition. Recently, FKBP12 has been reported to promote osteoblastic differentiation by activating the bone morphogenetic protein (BMP) receptor (3234). Our current studies have shown that F alone increased SDF-1 in the transplant, and we have found in previous studies that cells with macrophage phenotypes are liberated from the bone marrow by FK506 (27).…”
Section: Discussionmentioning
confidence: 99%